2014
DOI: 10.1111/ijs.12329
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Surgical Decompression for Space-Occupying Middle Cerebral Artery Infarction: Systematic Review

Abstract: Most patients treated with surgical decompression for space-occupying infarction have a reasonable quality of life at long-term follow-up and are satisfied with the treatment received. Severe depressive symptoms are uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
2
29
1
Order By: Relevance
“…The majority of patients who enter these new states of disability and impairment, however, can find new meaning and happiness during this period of adjustment. 74 Health-Related Quality of Life Stroke patients and families often report lower HRQOL than nonstroke patients, and HRQOL is correlated with the severity of the stroke. 1,75 Particular attention is needed for young children, older patients, and those with impaired communication because they are at highest risk for inadequate assessment and symptom management.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…The majority of patients who enter these new states of disability and impairment, however, can find new meaning and happiness during this period of adjustment. 74 Health-Related Quality of Life Stroke patients and families often report lower HRQOL than nonstroke patients, and HRQOL is correlated with the severity of the stroke. 1,75 Particular attention is needed for young children, older patients, and those with impaired communication because they are at highest risk for inadequate assessment and symptom management.…”
Section: Adverse Eventsmentioning
confidence: 99%
“…[12][13][14][15][16] Our own stratification was informed by multiple independent studies of physicians, nurses, and the general public in which 6%-38% of respondents considered mRS 4 a quality of life worth living. 12,13,15,16 Nonetheless, retrospective studies have shown that most MCI patients who have undergone DC have a reasonable quality of life and are satisfied with their treatment, even those with an mRS of 4, [33][34][35] creating an inherent difficulty in defining acceptable outcomes. Therefore, our findings should not be applied rigidly, but rather serve as a framework for clinical decision-making based upon individual patient and family goals of care.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review suggested that the quality of life (QoL) at long-term follow-up is only moderately decreased when compared with the general population and that the vast majority of patients are satisfied with the treatment received [97]. Interestingly, only one third of neurologists estimated that the majority of patients with MMI had an acceptable QoL based on Fig.…”
Section: How About Quality Of Life?mentioning
confidence: 99%
“…Please note that this flowchart is only illustrative and often times these steps happen simultaneously as any delay in appropriate treatment may impact outcomes the severity of expected deficits [98]. This may suggest that patients' resilience and ability to adapt to a significant deficit are greater than physician expectations and that other factors than mental and physical health like social status and support network may play significant roles [97]. In addition, recent evidence suggests that QoL and functionality in activities of daily living continue to improve beyond the initial year survived [99].…”
Section: How About Quality Of Life?mentioning
confidence: 99%